Impact And Reasons For The Apathy In The 2019 General Elections: The Part Played By Inec, Problems, And Nigeria's Future. - Ajiteru,S.A.R; Sulaiman T.H; Abalaka, J.N (International Forum of Researchers and Lecturers, 2025)
These tests assessed the electorate's degree of disinterest in voting. It investigated the reasons behind voters' indifference to voting. It also established the voting remedies disinterest from the viewpoints of the voters and, lastly, investigated how factors including socioeconomic position, political party affiliations, and educational attainment affected the voters' degree of voting apathy. The survey research design was used in the study. Using a purposive sampling technique, 350 electorates from seven faculties at Obafemi Awolowo University in Ile-Ife made up the sample size. Before being used, a tool called the Voting Apathy Questionnaire (VAQ) was created and verified. Three hypotheses were investigated and confirmed, and three research questions were posed and addressed. Among other things, the results indicated that 50.3% of voters were indifferent to voting. Additionally, the degree of voting indifference among the electorate was significantly influenced by educational levels (² = 161.969a, p < 0.05). Rational Choice Theory was selected as the theoretical underpinning, and the study used both survey research design and secondary sources of data collection as information gathering techniques. The results showed that low levels of education and illiteracy are associated with poor political and voter education, particularly when it comes to the fact that the majority of voters (roughly 50%) fail to pick up their permanent voter cards and are therefore unable to be accredited to vote; that Nigerian politics is another factor, as it is known as a bitter and acrimonious politics; and that because elected officials have failed to fulfill their campaign promises, the electorate has lost faith in the government and finds it difficult to participate in the electoral process.